2015
DOI: 10.1021/acsnano.5b05819
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Capacitance Variation in Sub-nanometer Pores by in Situ Tuning of Interlayer Constrictions

Abstract: The contribution of subnanometer pores in carbon electrodes to the charge-storage mechanism in supercapacitors has been the subject of intense debate for over a decade. Here, we provide a model system based on graphene oxide, which employs interlayer constrictions as a model for pore sizes that can be both controllably tuned and studied in situ during supercapacitor device use. Correlating electrochemical performance and in situ tuning of interlayer constrictions, we observe a peak in specific capacitance when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 53 publications
(145 reference statements)
5
43
1
Order By: Relevance
“…It has been shown that the maximum volumetric capacitance was achieved when the carbon pore size matched that of the adsorbing electrolyte ions. [25][26][27][28][29] The development of in situ experimental techniques, including the electrochemical quartz crystal microbalance [30][31][32] (EQCM) and small-angle X-ray scattering [33][34][35] (SAXS), has radically modified understanding of charge storage mechanisms and ion dynamics in nanoporous carbon-based supercapacitors in aqueous electrolytes. Recently, Prehal et al [33] used SAXS to characterize ion adsorption mechanisms in confined pores and the effects of different microporous carbons on the capacitance.…”
Section: Doi: 101002/smll201801897mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the maximum volumetric capacitance was achieved when the carbon pore size matched that of the adsorbing electrolyte ions. [25][26][27][28][29] The development of in situ experimental techniques, including the electrochemical quartz crystal microbalance [30][31][32] (EQCM) and small-angle X-ray scattering [33][34][35] (SAXS), has radically modified understanding of charge storage mechanisms and ion dynamics in nanoporous carbon-based supercapacitors in aqueous electrolytes. Recently, Prehal et al [33] used SAXS to characterize ion adsorption mechanisms in confined pores and the effects of different microporous carbons on the capacitance.…”
Section: Doi: 101002/smll201801897mentioning
confidence: 99%
“…Following this study, the origin of the anomalous increase in capacitance has received considerable attention. It has been shown that the maximum volumetric capacitance was achieved when the carbon pore size matched that of the adsorbing electrolyte ions . The development of in situ experimental techniques, including the electrochemical quartz crystal microbalance (EQCM) and small‐angle X‐ray scattering (SAXS), has radically modified understanding of charge storage mechanisms and ion dynamics in nanoporous carbon‐based supercapacitors in aqueous electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…water and acetonitrile). [21][22][23] Moreover, the sizes of slit pores provided by the interlayers of GO are "flexible" as they depend on the nature of the solvent along with the sizes of intercalated ions/molecules. 2,[24][25][26][27][28] Graphite/graphene oxides are commonly produced via the strong oxidation of graphite (e.g., using the Brodie or Hummers methods 29,30 ) and inherit the layered structure of pristine graphite.…”
Section: Introductionmentioning
confidence: 99%
“…Completely dried GO was used for further characterization and supercapacitor electrode fabrication. As produced, completely dried GO was characterized using different complementary methods 2 and used for activated carbon (AC)/r-GO electrode fabrication. The results clearly confirmed the successful fabrication of GO decorated with hydroxyl, carbonyl, ether, and carboxyl groups, which in its restacked dried form keeps an interlayer distance of ∼0.79 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Because electrode materials are the key components to the performance of supercapacitors, rationally designing and fabricating high-quality electrode materials play a decisive role in developing next-generation high-performance supercapacitors. 24 …”
Section: Introductionmentioning
confidence: 99%